SOME ASPECTS OF THE CONDUCT CREDIT-MODULAR LEARNING SYSTEMS - H.M. Martyanova (Academy of Cognitive and Natural Sciences, 2022)
In article the didactics opportunities of introduction of elements of credit modular training in vocational training the teacher of music are considered; mechanisms of integration the general-didactic and individual-methodical are isolated. Didactics opportunities of a method of testing are analyzed during an estimation of results of performance of educational tasks.